Awesome Blossom - Myracle, Lauren (Amulet Books, 2013)
Fifth-grade best friends Katie-Rose, Milla, Yasaman, and Violet are determined to save a new student from Modessa's evil influence, but Katie-Rose is busy not flirting with Preston and all four are distracted by trying to organize Yasamin's sister's birthday party